Lymphoepithelial cyst on the tongue: A case report - Nami Nakayama; Satoshi Nakamura; Keisuke Sawada; Yosuke Iijima; Shunsuke Hino; Takahiro Kaneko; Norio Horie (Oral and Maxillofacial Surgery Cases, 2023)
Lymphoepithelial cyst of the oral cavity is a rare cyst, and histopathologically is generally lined by parakeratinized stratified epithelium, showing lymphoid tissue in the submucosal connective tissue. We report herein a case of lymphoepithelial cyst on the lateral border of the tongue. The patient was a 73-year-old woman. Intraoral examination revealed an asymptomatic, yellowish-white mass on the left border of the tongue. The mass was excised under local anesthesia and the histopathological diagnosis was lymphoepithelial cyst. We present a rare case of lymphoepithelial cyst on the lateral border of the tongue with a brief discussion of the differential diagnoses.